Anti-SARS-CoV-2 Antibodies Testing in Recipients of COVID-19 Vaccination: Why, When, and How? - Lippi, Giuseppe; Henry, Brandon Michael; Plebani, Mario (Diagnostics (Basel), 2021)
Although universal vaccination is one of the most important healthcare strategies for limiting SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) circulation and averting the huge number of hospitalizations and deaths due to coronavirus disease 2019 (COVID-19), significant inter-individual variability of COVID-19 vaccines’ efficacies has been described, mostly due to heterogeneous immune response in recipients. This opinion paper hence aims to discuss aspects related to the opportunity of monitoring anti-SARS-CoV-2 antibodies before and after COVID-19 vaccination, highlighting the pros and cons of this strategy. In summary, the advantages of anti-SARS-CoV-2 antibodies’ testing in recipients of COVID-19 vaccination encompass an assessment of baseline seroprevalence of SARS-CoV-2 infection in non-vaccinated individuals; early identification of low or non-responders to COVID-19 vaccination; and timely detection of faster decay of anti-SARS-CoV-2 antibody levels. In contrast, potential drawbacks to date include an unproven equivalence between anti-SARS-CoV-2 antibody titer, neutralizing activity, and vaccine efficiency; the lack of cost-effective analyses of different testing strategies; the enormous volume of blood drawings and increase of laboratory workload that would be needed to support universal anti-SARS-CoV-2 antibodies testing. A potential solution entails the identification of cohorts to be prioritized for testing, including those at higher risk of being infected by variants of concern, those at higher risk of unfavorable disease progression, and subjects in whom vaccine immunogenicity may be expectedly lower and/or shorter.